Islamic Values-Based Reconstruction of Community Organizations Governnce : The Context of Balancing Freedom of Association and Public Order in Indonesia - Teguh Luhuringbudi; Tri Gunawan; Edi Kurniawan; Nabilah Yusof @ Abdul Rahman; Wilnan Fatahillah; Safa Husayn Alrumayh (International Forum of Researchers and Lecturers, 2026)
Non-Indexed Publication